Analisis Semantik Leksikal Berbasis Teori Katz dan Fodor Terhadap Makna Surah Adh Dhuha - Syahri, Hanifa; Siregar, Husnatul Hamidiyyah (INCARE, International Journal of Educational Resources, 2025)
This study aims to examine the linguistic and spiritual meanings of Surah Adh-Dhuha by employing the framework of conceptual semantics as proposed by Katz and Fodor. Surah Adh-Dhuha is selected due to its gentle, affirmative, and emotionally supportive language, which plays a significant role in spiritual and emotional healing. This research adopts a qualitative descriptive method, focusing on the semantic analysis of key lexical items in the verses of Surah Adh-Dhuha, such as adh-dhuha, al-layl, m? waddaka, and wa la al-?khiratu khayrun laka. The analysis is conducted by identifying semantic markers and distinguishers, as well as paradigmatic and syntagmatic relations among lexical units based on Katz and Fodor’s semantic theory. The findings reveal that the vocabulary of Surah Adh-Dhuha conveys not only denotative meanings but also complex conceptual structures that embody hope, emotional reassurance, and spiritual restoration. The semantic opposition between light and darkness, presence and absence, and present hardship and future promise contributes to the therapeutic function of the surah. This study concludes that the Qur’anic language of Surah Adh-Dhuha possesses a healing dimension that can be systematically explained through linguistic semantic analysis.